Learning Writing by Paraphrasing the Quotations on SFL - Edy Suseno (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2020)
Writing is one of the language skills. Nevertheless, most EFL students got a problem with writing. It provokes their hindrance in learning English. The lack of vocabulary and competence in adapting grammar rules are the agent to worsen their writing ability. Comprehending the text is a kind of way to help the students build their vocabulary knowledge. The words they learn can be adapted to study grammar through GTM. They are essential to better their practical ability in descriptive text. It is the implementation of the SFL theory. Practicing descriptive text supported by adapting reading comprehension and GTM develops the students’ competence to paraphrase the text. Paraphrasing through SFL enhances writing skills.